Frequency and types of congenital heart disease in neonates: A cross-sectional study from large public sector hospital of Karachi, Pakistan (Journal of Fatima Jinnah Medical University, 2020)
Background: Congenital heart disease (CHD) is one of the frequent congenital health issues in neonates. Early diagnosis is a key factor to combat this problem. This study aims to assess the frequency and common types of CHD among neonates presenting to a tertiary care hospital, Karachi.Patients and methods: This descriptive cross-sectional study was conducted in a Neonatal Intensive Care Unit (NICU) of National Institute of Child Health (NICH), Karachi from March to September 2017. All neonates of gestational age ≥37 weeks with suspected CHD (presence of blue-tinged skin, i.e. cyanosis on routine clinical examination) were included. Information regarding presence of CHD and its types were collected along with the demographic characteristics and history of the patients.Results: Of 134, frequency of CHD was observed in 126 (94%) patients. Out of these 126 CHD patients, Ventricular septal defect (VSD) was observed in 49 (38.9%), patent ductal arteriosus (PDA) in 29 (23%), atrial septal defect (ASD) was observed in 19 (15.1%), Transposition of great arteries (TGA) in 18 (14.3%), and tetralogy of Fallot (TOF) in 14 (11.1%) patients. A significant association of VSD was observed with neonatal age (p =
Keywords: Congenital heart diseases; Neonates; NICU